Dampak Inflasi terhadap Keuntungan Usaha Mikro (UMKM) di Lingkungan Pasar - Reni Dwi Fitriani; Articha Zahra; Ressa Arif Fadhilah; M.Yusuf Bahtiar (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2026)
This study aims to analyze the impact of inflation on the profitability of Micro, Small, and Medium Enterprises (MSMEs) operating in traditional markets. Inflation influences key business aspects, including rising production costs, declining consumer purchasing power, and instability in input prices, all of which can disrupt business performance. The research employed a quantitative approach using survey data collected from MSME actors to assess these effects. The findings reveal that inflation has a significant negative impact on MSME profitability, particularly through the reduction of profit margins. This occurs as businesses face higher raw material costs while simultaneously experiencing a decline in sales volume due to weakened consumer demand. As a result, many MSMEs struggle to maintain financial stability and sustain their operations under inflationary pressure. These findings highlight the need for adaptive strategies among MSMEs, such as cost efficiency and pricing adjustments. Additionally, the study offers important policy implications for the government to support MSMEs through targeted interventions, including price stabilization measures and financial assistance programs, in order to maintain business resilience and economic sustainability.